Efeito do aquecimento e do uso do solo sobre a comunidade de protistas ciliados planctônicos. - Santana, Loiani Oliveira (2023)
Anthropogenic actions have contributed significantly to the increase in temperature and the addition of nutrients to aquatic bodies. Among the organisms that make up the aquatic microbiota, ciliated protozoa are able to respond quickly to environmental changes imposed on these systems. Thus, the objective of this work was to experimentally investigate the effects of warming and nutrient enrichment on the patterns of richness, density and species composition of the ciliate community, using mesocosms as a model system. Effects on all attributes studied were produced only by nutrient enrichment, while changes in temperature and detritus concentration did not produce significant changes in the community. It is suggested that the bottom up effect is probably the control mechanism that is prevailing in the structuring of the community of ciliate protists in this study, as the high nutrient load is probably providing greater availability of niches, through food resources, which favor the increase the abundance and richness of protists.